Clinical Assessment and Management of Portal Hypertension - Kibrit, Jacob; Khan, Ruben; Jung, Barbara H.; Koppe, Sean (Seminars in Interventional Radiology, 2018)
The development of portal hypertension in a patient with cirrhosis portends a poor prognosis. Untreated or progressive portal hypertension has serious clinical outcomes, which are often fatal. It is important to recognize portal hypertension early to delay progression and to treat complications of portal hypertension as they arise. This review will focus on the clinical assessment and management of portal hypertension.
Keywords: portal hypertension; hepatic venous pressure gradient; esophageal varices; ascites; encephalopathy